Adventures in sound. Rhoda Power, archaeology and BBC Schools Radio, 1941–1945. - Lewis, Jan (Women's History Review, 2025)
This paper examines the collaboration between BBC radio producer Rhoda Power and professional archaeologists Dina Dobson and Jacquetta Hawkes, in the production of the Schools radio series How Things Began. During the Second World War, radio became an important way of conveying educational information to the citizens of Britain. At the same time, archaeology was consolidating its role in British public life. The discussion considers the techniques used by Rhoda Power and expert contributors in the creation of archaeological radio content designed to appeal to school children, and therefore contributes to an enhanced understanding of Rhoda Power's role within the BBC Schools service, and provides new insights into the contribution to British life and education of two eminent female archaeologists.